The touch of the sacred : the practice, theology, and tradition of Christian worship - Immink, Gerrit (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2014)
All over the world Christian communities meet on Sunday morning for worship. But what really happens during a worship service? How do worshipers participate in the service? What does it mean to sing, pray, and celebrate the Lord's Supper together? What do worshipers do when they listen to a sermon? In The Touch of the Sacred Gerrit Immink offers thoughtful theological reflection on the religious practice of worship services in the Protestant tradition. He develops a theology of worship with a clear focus on the death and resurrection of Jesus Christ as he explores the meaning of worship, the mystery of Christ, the sacraments, prayer, and preaching. Ultimately, he says, something dynamic happens when a church congregation speaks and acts: it is touched by the sacred, by a very encounter with the living God.
Worship as religious praxis. Worship as a communal act ; The agenda and script of worship ; The performance of worship ; Worship as true mediation? -- Sharing in salvation. Salvific facts and spiritual participation ; The Christian year ; The prayer for the presence of the Holy Spirit (epiclesis) ; The participation -- The mystery of Christ. The resurrection of Christ ; The ontological character of the resurrection ; A liminal event and an independent person -- Backgrounds and dilemmas. The Lord's supper : a departure from tradition? ; The word of God and the sermon ; Baptism and confession -- Prayer. Prayer as a religious praxis ; Liturgical prayer ; The prayers in the worship service -- Preaching. The act of participation ; The scriptures in the performance ; The rhetorical form of the sermon -- Celebrating the Lord's supper. Protestant communion practices ; The origin of the reformed liturgy of the Lord's supper ; Theology and piety in the reformed communion praxis ; Comparison with the sacrifice of the mass ; Contemporary praxis.
Includes bibliographical references (pages 252-263) and indexes.
Translated from the Dutch.
Keywords: Jesus Christ -- Person and offices; Theology, Practical; Worship; Spiritual life -- Christianity; Salvation -- Christianity